Results of the Territorial Program “Development of products and health services” - Nadina Travieso Ramos; Sara Riccis Salas Palacios (Medisan, 2024)
A science, technology and innovation program is a group of activities organized in projects that are related to each other, which objective is to solve a problem identified according to the priorities and directed to achieve results of specific impacts. In Santiago de Cuba province the Territorial Program "Development of products and health services" is in action since 2020, which has implemented 12 investigation projects. In this work the scientific-technical results are identified; also, it is considered that they respond to sectoral and territorial priorities and are in correspondence with the policy of the health sector and higher education in Cuba. Their introduction contributes to solve the health problems in the territory by means of the implementation of science and technological innovation for the diagnosis, treatment and rehabilitation of persons with diseases.